2021
DOI: 10.1186/s12879-021-05788-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiple drug resistance of Campylobacter jejuni and Shigella isolated from diarrhoeic children at Kapsabet County referral hospital, Kenya

Abstract: Background Diarrhoea is a common cause of mortality and morbidity in children under five years old. In Kenya, it has a 21% case fatality with Enteropathogenic E. coli, Campylobacter jejuni, Shigella spp. and Salmonella spp. accounting for 50–60% of the cases. Sulphonamides, tetracycline, ampicillin and trimethoprim/sulfamethoxazole are typically used in the treatment of diarrhoeal diseases but have become ineffective in the face of emerging antimicrobial resistance. The objective of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
2
14
1
Order By: Relevance
“…The overall prevalence of C. jejuni was calculated at 14.8%. This nding was comparable with other studies reported in Jimma Ethiopia [23] and Gondar Ethiopia [13], kenya [24] with the isolation rates of 11.9% and 14%, 12.9% respectively. However, the present study showed higher prevalence compared to other African studies conducted in Sudan, 2% [38], Burkina Faso, 1.1% [39] and Zambia,3.5% [40].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The overall prevalence of C. jejuni was calculated at 14.8%. This nding was comparable with other studies reported in Jimma Ethiopia [23] and Gondar Ethiopia [13], kenya [24] with the isolation rates of 11.9% and 14%, 12.9% respectively. However, the present study showed higher prevalence compared to other African studies conducted in Sudan, 2% [38], Burkina Faso, 1.1% [39] and Zambia,3.5% [40].…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of C. jejuni infection among U5C vary geographically. For instance, the prevalence of C. jejuni was 4%, 7.7%, 8.4%, 8.9%, 11.9%, 12.9% and 14% in the study from India, Brazil, Poland, Jimma Ethiopia, Kenya, and Gondar Ethiopia, respectively [13,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…caused bloody diarrheal constituted 16.2% of the total diarrheal Consistency (26) . On another hand, Compared to a study conducted by Zachariah et althe rate varies significantly the highest percentage being mucous (68%) and the lowest ratio (18%) of watery (27) .…”
Section: Discussionmentioning
confidence: 54%
“…Shigellosis remains a common, serious, and increasingly difficult-to-treat disease, especially because of the emergence of antibiotic-resistant strains [1][2][3][4]. For example, a survey in 2016 showed that there were an estimated more than 269 million cases of shigellosis with over 212,000 deaths, of which about 74 million cases of shigellosis were in children younger than 5 years old and caused more than 63,000 deaths [5].…”
Section: Introductionmentioning
confidence: 99%